Snake venom Lys49 myotoxins: From phospholipases A2 to non-enzymatic membrane disruptors - Lomonte, Bruno (2012)
Snake venoms often contain toxins that cause a rapid necrosis of skeletal muscle fibers, referred to as myotoxins. The most common among them are phospholipases A2 (PLA2s), enzymes that have two independent evolutionary origins in snake venoms. Within the group II PLA2s found in viperid venoms, a particular subgroup emerged, in which the otherwise conserved Asp49 of their catalytic center is replaced by Lys49. These intriguing proteins, referred to as Lys49 myotoxins, lost the ability to catalyze phospholipid hydrolysis, but still induce myonecrosis by a non-enzymatic mechanism based on membrane permeabilization as the critical event. Such mechanism is only partially understood. This review briefly describes the general structural and functional characteristics of the Lys49 myotoxins, and summarizes four proposed models of their functional “toxic site”. Finally, it discusses some novel insights into their mode of action, in particular examining arguments and experimental observations that could shed light on the possible nature of their membrane target on skeletal muscle cells, which remains elusive.